CienTec Guide: Application and Online Evaluation of a Context-Based Recommender System in Cultural Heritage - Laskoski, Felipe F.; Goldman, Alfredo (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2022)
A Recommender System (RS) is best applied in situations where users have to decide to choose among a list of usually many options and visits in cultural heritage sites are an example of that. Visitors may also face problems in finding how to reach their options. This research addresses both problems with a mobile app consisting of a hybrid context-based RS that suggests personalized visiting routes with the goal to maximize user satisfaction and minimize the length of the recommended route. Unlike most published RS papers related to cultural heritage, the system in this research was built for the mobile platform and its effectiveness was evaluated with actual visitors of a museum. The results were consistent in indicating the improved system achieved high user satisfaction, with all the recommender attributes average ratings between 4.3 and 4.7 (in a scale of 1 to 5), and accuracy, with a Mean Average Error (MAE) of 0.69.